Enhanced CH4 storage in hydrates with the presence of sucrose stearate - Shi, Lingli; Ding, Jiaxiang; Liang, Deqing (Energy, 2019)
Clathrate hydrate is a promising option for gas storage and transportation. Sucrose stearate, an environmentally friendly chemical, was studied in CH4 hydrate formation process to evaluate its effect on gas storage of CH4 hydrate. The experiment was conducted systematically with four different sucrose stearate concentrations at three various initial pressures. The experimental data were employed to calculate the normalized hydrate formation rate and equilibrium time based on chemical affinity. The results indicated that the presence of sucrose stearate significantly enhanced the CH4 hydrate formation rate and storage when initial pressure was higher than 5.0 MPa. In addition, Raman spectroscopic analysis was performed to examine the hydrate structure and obtain the theoretical storage capacity. The spectra demonstrated that sucrose stearate decreased the hydration number with not changing CH4 hydrate's structure. The theoretical storage capacity and the energy value were increased by about 2.59%. Combing all the results, sucrose stearate was a good kinetic promoter for CH4 hydrate formation. The systems with sucrose stearate at low concentration and high concentration were suggested for designing gas storage process and fast hydrate formation process, respectively. (C) 2019 Elsevier Ltd. All rights reserved.